Integration analysis of pituitary proteome and transcriptome reveals fertility–related biomarkers in FecB mutant Small Tail Han sheep - Wang, Xiangyu; Guo, Xiaofei; He, Xiaoyun; Di, Ran; Zhang, Xiaosheng; Zhang, Jinlong; Chu, Mingxing (Frontiers in Endocrinology, 2024)
The Booroola fecundity mutation (FecB) in Small Tail Han sheep has been shown to enhance ovulation rates and litter sizes by affecting the hypothalamic-pituitary-gonadal (HPG) axis. Despite the pituitary's role in reproductive regulation, its involvement in FecB-induced ovulation remains understudied. Our study aimed to fill this gap by analyzing pituitary tissues from FecB homozygous (BB) and wild-type (WW) ewes during luteal and follicular phases using tandem mass tag-based protein quantification and the DIABLO framework for proteomic and transcriptomic data integration. Significant differences in 277 proteins were observed across estrus periods, with network analysis highlighting the voltage-dependent calcium channel L-type alpha-1C as a key convergence point in oxytocin signaling and GnRH secretion pathways. The DIABLO method revealed a strong correlation (0.98) between proteomic and transcriptomic datasets, indicating a coordinated response in FecB ewes. Notably, higher expression levels of Follicle Stimulating Hormone Subunit Beta (FSHB) and Luteinizing Hormone Subunit Beta (LHB) were found in BB ewes during the follicular phase, potentially due to elevated E2 concentrations. Furthermore, our analysis identified genes related to the Gamma-aminobutyric acid type A receptor family (GABRA2, GABRG1, GABRB1) in the pituitary, with GABRB1 showing higher expression in BB ewes. This suggests a role for GABA in modulating GnRH and gonadotropin feedback loops, potentially contributing to the FecB mutation's effect on ovulation. This study provides novel insights into the pituitary's role in fertility among FecB sheep, identifying GABA as a potential regulatory factor within the HPG axis. The findings also open avenues for discovering new biomarkers in pituitary endocrinology for sheep breeding purposes.